GAMBARAN PENGEMBANGAN PROGRAM STUDI PENDIDIKAN AGAMA ISLAM (PAI) PADA FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - ., Rosdiana (Universitas Islam Negeri Alauddin Makassar, 2017)
This study examines the prospect of developing the study program of Islamic Education (PAI) at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. Focused on two sub issues, namely: (1) Efforts to develop PAI study program at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar; (2) Supporting factors and inhibiting the development of PAI Faculty of Tarbiyah and Teacher Training Program UIN Alauddin Makassar. The type of research is qualitative with managerial, phenomenological and sociological approach. The data sources consist of documentation on PAI Study Program, Alumni of PAI study program, staff, and lecturer of Faculty of Tarbiyah and teacher of UIN Alauddin Makassar as informant. Data collection using interviews, documentation, and observation. Technique of analysis / data processing in three ways, namely data reduction, data display, and data verification. Test the validity of informant data by using triangulation.The result of the research shows that there are five efforts conducted by managers in the development of PAI study program at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar, namely: (1) Efficiency and effectiveness of leadership; (2) Program evaluation and graduate tracking; (3) Program development planning; (4) Cooperation and partnership; (5) Program evaluation on the experience and quality of student learning. Factors supporting the development of PAI study program at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar, namely: (1) Experience in development; (2) Quality of lecturer; (3) Government support; (4) Many enthusiasts (student quantity). While the inhibiting factors are (1) Infrastructure is not yet complete; (2) Unsatisfactory lecturer discipline; (3) Source of fund has not been socialized (Faculty).The implication of this research is the need to systematize the learning process in accordance with the needs of the alumni of PAI study program and require support from all parties, namely the cooperation that is considered to be competent in the field including the Ministry of Religious Affairs in the field of Mapenda. In order to formulate and realize the learning that has character, methodological, skilled, has the value of Qurani, scientific, educational and can be developed based on the curriculum of learning. The management of learning can not be separated from the facility of study program, lecturer competence, students and organization of study program of PAI who have successfully obtained accreditation A.